Analysis of Secondary Metabolite Compounds of Papaya Leaf Extract (Carica papaya L.) and Noni Leaf Extract (Morinda citrifolia L.) as Neuroprotective Agents in Alzheimer's Disease - Amaliyah, Nasywa Sayyida; Rizal, Cinta Amanatur; Andiarna, Funsu; Agustina, Eva; Purnamasari, Risa; Lusiana, Nova; Hidayati, Irul (International Conference on Sustainable Health Promotion, 2025)
Alzheimer's disease is a neurological disorder associated with the accumulation of amyloid proteins in the brain. Papaya (Carica papaya L.) and noni (Morinda citrifolia L.) are known as natural sources with high antioxidant activity, which have the potential to function as neuroprotective agents. This study aims to identify secondary metabolites and evaluate the antioxidant activity of ethanol extracts from papaya and noni leaves. Extraction was performed using the maceration method with 40% ethanol. Phytochemical testing was performed qualitatively with several reagents appropriate for testing each compound. Phytochemical screening revealed that papaya and noni leaf extracts contain similar secondary metabolite compounds, namely alkaloids, flavonoids, phenolics, tannins, saponins, and triterpenoids. However, only papaya leaf extract showed the presence of steroid compounds, indicating a difference in the composition of secondary metabolites that could potentially affect the activity of each extract as a neuroprotective agent in Alzheimer's disease.